(untitled) (Revista Peruana de Investigación Educativa, 2011)
The work reflects upon two research lines being carried out in Argentina in a research programme: On the one hand, it focuses on studying the particular characteristics in which students build up their learning within school and out-of-school contexts; on the other hand, although closely related to this, it focuses on highlighting the students’ voices according to a theoretical and methodological tradition which attempts to position students actively in educational research. Within a cualitative etnographical approach, the research team developed a “learning diary” with students’ groups of a Secondary School. Students’ feelings, emotions, thoughts, voices, and silences become outstanding and key factors around school and out-of-school learning processes.